Evaluation of National Health Insurance Program Policies by Ketapang District Health Social Security Administration Body - Sukamto, Sukamto; Rupita, Rupita; Herlan, Herlan; Arifin, Arifin; Erdi, Erdi (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to evaluate the process of implementing the National Health Insurance program policy by the Ketapang District Health Social Security Administering Agency, based on a compliance perspective relating to compliance with implementing agents, implementation of policies and facilities and resources, and based on what happening Perspective, which is related to factors that influence implementation and short-term outcomes. The results of this research show that the Evaluation of the National Health Insurance program policy implementation process by the Ketapang District Health Social Security Administration Agency has yet to be implemented optimally. This can be seen from the following indicators: Compliance perspective, which includes compliance by policy implementing agents, has not been carried out objectively according to regulations and is not by standards and procedures established by policy. Policy implementationNational Health Insurance Program by the Ketapang District Health Social Security Administering Agency has not been able to improve the quality of health services in Ketapang Regency, the availability of health facilities and resources has not met the criteria for capitation payment norms, and there is a lack of health workers both in terms of quality and quality. Meanwhile, the What is Happening Perspective includes factors that influence the implementation of policies, namely the actors involved, clarity of policy objectives, program complexity, support from all units involved, and other factors such as human resources, which include the quality and quantity and weak authority and legitimacy of health workers and short-term results have not been achieved due to contact data on the online application of the Social Security Administering Agency for Health.